DIALECTOLOGY: DIALECTS OF THE UZBEK LANGUAGE AND THEIR CHARACTERISTICS - Yuldasheva Dilnoza Bekmurodovna; Qurbonov Bekzod Gʻanisher oʻgʻli; Muxammadov Javoxir Oblaqul oʻgʻli (Web of Journals Publishing, 2024)
This article explores the dialects of the Uzbek language, delving into their linguistic characteristics, regional distribution, and the factors influencing their development. Dialectology, the study of dialects, is crucial in understanding the internal variations within a language, and this paper aims to map the distinct dialectical divisions within the Uzbek language. The article analyzes the phonetic, morphological, and syntactic features that differentiate various Uzbek dialects, paying attention to historical, geographical, and social factors that have contributed to these variations. It also discusses the impact of standardization efforts on regional dialects and the preservation of linguistic diversity. By examining the dialects of Uzbek, this study contributes to the broader field of sociolinguistics and language planning.
Keywords: Dialectology, Uzbek language, dialects, linguistic characteristics, phonetic features, morphological features, syntactic features, sociolinguistics, regional variations, language standardization.